Apa antigen of Mycobacterium avium subsp. paratuberculosis as a target for species-specific immunodetection of the bacteria in infected tissues of cattle with paratuberculosis - Souza, Giliane S. (2011)
Comparative genomics of Mycobacterium spp. have revealed conservative genes and respective proteins differently expressed in mycobacteria that could be used as targets for the species-specific immunodiagnostics. The alanine and proline-rich antigen Apa is a mycobacterial protein that present significant variability in primary sequence length and composition between members of M. avium and M. tuberculosis complexes. In this study, the recombinant Apa protein encoded by the MAP1569/ModD gene of M. avium subsp. paratuberculosis (Map) was used to generate a panel of monoclonal antibodies which were shown to recognize the most important veterinary pathogens of the M. avium complex, specifically Map and M. avium subsp. hominissuis, and which did not cross-react with M. bovis or M. tuberculosis. The produced antibodies were demonstrated to be a useful tool for the species-specific immunofluorescence or immunohistochemical detection of Map in experimentally infected cell cultures or intestinal tissues from cattle with bovine paratuberculosis and, additionally, they may be employed for the discrimination of pathogenic M. avium subspecies via Western blotting.